Risk analysis and controllability of credit market - Razakanirina R. M.; Chopard B. (ESAIM: Proceedings and Surveys, 2015)
In this paper we present the behaviours of a simple credit market model built upon a static directed complex network topology. We found that the market structure plays a key role on the stability of such a model. Cyclic topologies accumulate more debt than acyclic ones, and when the total cash is less than the total debt, the market becomes unstable and exhibits chaotic behaviour. Exogenous creation of currency is used to control the market stability. Two regimes of control emerge depending on the credit market structure. First, power law control is needed for acyclic random topologies built upon Erdos-Rényi and Barabasi-Albert algorithms. Second, exponential control is needed to stabilize cyclic market built with the Watts-Strogatz algorithm.